KKL correlation for simulation of nanofluid flow over a stretching sheet considering magnetic dipole and chemical reaction. Issue 11 (8th June 2021) - Punith Gowda, R. J.; Naveen Kumar, R.; Jyothi, A. M.; Prasannakumara, B. C.; Nisar, Kottakkaran Sooppy
Abstract: The enhancement of heat transfer is an important factor in heat exchangers, nuclear reactors, electric coolers and solar collectors. The enhance in rate of heat and mass transfer can be achieved by choosing suitable nanofluid or ferromagnetic fluid as an active liquid. In this connection, we have investigated the ferromagnetic nanofluid flow past a flat elastic sheet with porous medium and chemical reaction. Further, C u O − H 2 O nanofluid is considered and simulated through the Koo and Kleinstreuer‐Li (KKL) nanofluid model. The described governing equations are reduced to ordinary differential equations (ODE's) by means of apt similarity transformations and then they are numerically tackled using Runge Kutta Fehlberg‐45 (RKF‐45) scheme along with shooting method. The graphical results of the velocity, concentration and thermal profiles along with skin friction, Sherwood and Nusselt numbers are found to get an obvious insight of the existing boundary flow problem. The results reveal that, increasing values of ferromagnetic interaction parameter decays the velocity gradient but converse trend is depicted in thermal gradient due to the frictional heating between fluid layers. The increasing values of porosity parameter slowdowns the rate of heat transfer and velocity gradient. Abstract : The enhancement of heat transfer is an important factor in heat exchangers, nuclear reactors, electric coolers and solar collectors. The enhance in rate of heat and mass transfer can be achieved by choosing suitable nanofluid or ferromagnetic fluid as an active liquid. In this connection, we have investigated the ferromagnetic nanofluid flow past a flat elastic sheet with porous medium and chemical reaction. Further, C u O − H 2 O nanofluid is considered and simulated through the Koo and Kleinstreuer‐Li (KKL) nanofluid model.…